Analisis Pengaruh Current Ratio, Debt to Equity Ratio, Net Profit Margin dan Total Aset Turnover Terhadap Harga Saham pada Perusahaan Sektor Energi di Bursa Efek Indonesia Periode 2019-2022 - Budi Suhari; Mentiana Sibarani; Dhany Heryanto Soegieharto (Journal of Economics and Business UBS, 2023)
The aim of this research is to determine the influence of liquidity ratios, profitability, solvency and asset turnover ratios on share prices in energy sector companies on the Indonesia Stock Exchange. The phenomenon that occurred was when the energy sector stock index became the highest compared to other sectors throughout 2022, reaching 36 percent with growth of 2.1 percent. The sampling method for this research uses a purposive sampling method, where of the eighty-four energy sector companies, only thirty-two companies were selected that had complete financial reports for 2021-2022. The results of the research show that the variable factors Current Ratio and Debt to Equity Ratio partially have a negative effect on stock prices, while the variable factors Net Profit Margin and Total Asset Turnover ratios partially have a positive effect on stock prices. Meanwhile, simultaneously the variables Current Ratio, Net Profit Margin, Debt to Equity Ratio and Total Asset Turnover have a significant influence on share prices. It is hoped that future research will be able to determine the effect on stock returns.